PENGARUH PARTISIPASI PENGANGGARAN DAN INFORMASI ASIMETRI PADA SENJANGAN ANGGARAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI - Andy Mercury, Gede; Asri Dwija Putri, I G.A.M. (E-Jurnal Akuntansi, 2015)
This research has purpose to provide additional empirical evidence about the effect of budgetary participation and asymmetry information in budgetary slack with cultural organization as a moderating variable. This research sample consisted 46  stars hotels in Gianyar Regency. The data collection method that have been used is a questionnaires that distributed to the manager or head section/division that has a same level with the manager, this section has a functional in large role in used, management, and budgetary responsibility, also able to communicate with the subordinates and the top management, and participate as well with the wisdom that implemented by the  top management  in each of five stars hotel in Gianyar Regency. Data analysis tecnique that have been used is Moderated Regression Analysis (MRA). Based on the analysis results, it shows that budgetary participation and a symmetry information gives positive influences in budgetary slack. The interaction between budgetary participation with organization cultural be able to weaken the effect of asymmetry information in budgetary slack.
Keywords: budgetary participations; asymmetry information; cultural organization; budgetary slack